PENGARUH STRES, DISIPLIN, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN THE PAD BAR & GRILL LEGIAN BALI - Ni Ketut Tista Wulandari; I Wayan Mendra; Tjok Istri Harwathy (VALUES, 2021)
Human resources are the most important assets that must be owned by an organization and must be considered in management. Given the importance of the human resource factor, every business must try to improve the performance of its employees so that it is quality and productive to run the company. The fact is that the performance of employees in sales at The Pad Bar And Grill Legian-Bali has not been optimally realized. Factors that affect employee performance are job stress, work discipline and workload. This study aims to determine and analyze the effect of stress, discipline, and workload on the employee performance of The Pad Bar & Grill Legian Bali. This research was conducted at The Pad Bar & Grill Legian Bali. The population in this study were 32 employees of The Pad Bar & Grill Legian Bali. Determination of the sample in this study using a census method taken from the entire population, namely 32 respondents. Collecting data by distributing questionnaires using a Likert scale with a score of 1 to 5. The data analysis technique used is multiple linear regression analysis with the SPSS (Statistical Package Social Science) test version 21.